Pediatric Extrapolation in Type 2 Diabetes: Future Implications of a Workshop. Issue 1 (16th March 2020) - Barrett, Jeffrey S.; Bucci‐Rechtweg, Christina; Amy Cheung, S. Y.; Gamalo‐Siebers, Margaret; Haertter, Sebastian; Karres, Janina; Marquard, Jan; Mulugeta, Yeruk; Ollivier, Cecile; Strougo, Ashley; Yanoff, Lisa; Yao, Lynne; et al.
Abstract : Extrapolation from adults to youth with type 2 diabetes (T2D) is challenged by differences in disease progression and manifestation. This manuscript presents the results of a mock‐team workshop focused on examining the typical team‐based decision process used to propose a pediatric development plan for T2D addressing the viability of extrapolation. The workshop was held at the American Society for Clinical Pharmacology and Therapeutics (ASCPT) in Orlando, Florida on March 21, 2018.